Ignorance is bliss? An empirical analysis of the determinants of PSS usefulness in practice. (September 2020) - Jiang, Huaxiong; Geertman, Stan; Witte, Patrick
Abstract: Planning support systems (PSS) enabled by smart city technologies (big data and information and communication technologies (ICTs)) are becoming more widespread in their availability, but have not yet been fully recognized as being useful in planning practice. Thus, a better understanding of the determinants of PSS usefulness in practice helps to improve the functional support of PSS for smart cities. This study is based on a recent international questionnaire (268 respondents) designed to evaluate the perceptions of scholars and practitioners in the smart city planning field. Based on the empirical evidence, this paper recommends that it is imperative for PSS developers and users to be more responsive to the fit for task-technology and user-technology (i.e., utility and usability, respectively) since they positively contribute to PSS usefulness in practice and to be more sensitive to the potential negative effects of contextual factors on PSS usefulness in smart cities. The empirical analyses further suggest that rather than merely striving for integrating smart city technologies into advancing PSS, the way that innovative PSS are integrated into the planning framework (i.e., how well PSS can satisfy the needs of planning tasks and users by considering context-specificities) is of great significance in promoting PSS's actual usefulness. Highlights: This paper explores the determinants of PSS's actual usefulness via an international questionnaire survey. Three groups of factors—utility, usability and contextual factors—are identified. Results show that success factors (utility and part of usability) differ from failure factors (contextual factors). The use of PSS should satisfy the needs of planning tasks and users by considering context-specificities.